The complete mitochondrial genome of Hylarana latouchii (Anura: Ranidae) and its phylogenetic analysis. Issue 7 (3rd July 2021) - Sun, Yi-Jia; Zheng, Yue-Yue; Zheng, Wei-Cheng; Lin, Zhi-Hua; Qiao, Fen
Abstract: We reported the complete mitochondrial genome (mitogenome) of broad-folded frog ( Hylarana latouchii ). This mitogenome is 17, 007 bp in size and consists of 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and one non-coding sequence (D-loop). The total composition was 58.54% A + T and 41.46% G + C (T: 29.31%, C: 27.33%, A: 29.23%, and G: 14.13%). The phylogenetic analysis revealed that H. latouchii formed a clade with other two species of genus Hylarana . This mitogenomic sequence of H. latouchii provides useful data to study its population genetics and phylogeography.